Meningkatkan Kreativitas Berpikir Mahasiswa Biologi Terapan Bidang Inovasi Produksi Pangan dengan Penerapan Model Pembelajaran SFAE (Student Fasilitator and Explaining) - Nisa, Umi Mahmudatun; Pujiastutik, Hernik (Universitas Sebelas Maret, 2016)
This problem arises because of the low creative thinking in students in the course of Applied Biology food sector to produce innovative food, thereby solving the problem is to apply the learning model SFAE (Student Facilitator and Explaining) so that students are able to explore innovative ideas of stimulus explanations fellow students, because their subjects Applied Biology aims to make students able to apply the knowledge acquired during college biology. Formulation of the problem in this research is how the learning model SFAE (Student Facilitator and Explaining) can enhance students' creativity. This study aims to improve the creativity of the students so that they can provide innovative ideas and useful. This study with subjects younger students in 2012 academic year 2015/2016 odd semester to the University of PGRI Ronggolawe Tuban with the number of 30 people. The method used is descriptive explorative, which describes the state of the student after learning model application SFAE (Student Facilitator and Explaining). Instruments penggumpulan the data include observations made to determine how many students are able to produce a food product. The results were obtained from 30 students were divided into 6 groups, then obtained also 6 papers with creative ideas in terms of creating the processed food that has not been encountered in the community that is innovativeKey Word : Creativity Thinking, Food Innovation, Applied Biology, Learning Model SFAE